Analisis Perancangan Alat Pencacah Nilam Untuk Petani Nilam - Prananda, Fijay; Balaka, Ridway; Endriatno, Nanang (Teknik Mesin Universitas Halu Oleo, 2024)
The automatic pull shaft on the patchouli chopper is an important component of the patchouli chopper machine. The research aims to carry out an analysis of the patchouli chopper pull shaft and produce a design for the newest patchouli chopper. In this research, the focus was only on the analysis of the pulling shaft on the patchouli chopper where all research methodologies were carried out using inventor software. The main driving engine is a combustion engine with a power of 5.5 HP, S45C shaft material with a tensile strength of 58 kg/mm2, and a shaft diameter of 15 mm. In the selection of pulleys, plays with diameters of 50 mm and 300 mm are used, V - Belt speed is 0.18 m/s, circumference length is 1499 mm, using V - Belt type B with axle distance of 474.6 mm, the contact angle is 2.3 rad and the length of the chopped patchouli was 3.8 cm. From the calculations and analysis, the addition of a pulling shaft to the patchouli chopper is safe to use. Keywords: Patchouli chopping tool, Puller shaft, Patchouli